2016
DOI: 10.3109/14767058.2016.1169525
|View full text |Cite
|
Sign up to set email alerts
|

The influence of different maternal pushing positions on birth outcomes at the second stage of labor in nulliparous women

Abstract: In healthy nulliparous women, adopting a squatting position using bars was associated with a shorter second stage of labor, lower Visual Analog Scale score, more satisfaction, and a reduction in oxytocin requirements compared with adopting the supine position. For Turkish women, the squatting position is easy to adopt as it is more appropriate in terms of Turkish social habits and traditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 18 publications
4
46
4
2
Order By: Relevance
“…In the present study 38/200, 19% women opted out of the kneeling group as they were not comfortable in that position, this is higher than the 8% dropout rate reported by Regnar et al but lower than 49% reported by Gardosi et al 8,9 [15][16][17][18][19][20] However, some authors failed to observe any change in the second stage of labour whereas longer labour duration has also been reported by others. [9][10][11][12][13][14] Cochrane pregnancy childbirth systemic review of randomized trials by Gupta et al reported a small but significant decrease of second stage duration in women delivering in the upright position (all combined) compared to supine position, -6.16; 95% CI -9.74, -2.59.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…In the present study 38/200, 19% women opted out of the kneeling group as they were not comfortable in that position, this is higher than the 8% dropout rate reported by Regnar et al but lower than 49% reported by Gardosi et al 8,9 [15][16][17][18][19][20] However, some authors failed to observe any change in the second stage of labour whereas longer labour duration has also been reported by others. [9][10][11][12][13][14] Cochrane pregnancy childbirth systemic review of randomized trials by Gupta et al reported a small but significant decrease of second stage duration in women delivering in the upright position (all combined) compared to supine position, -6.16; 95% CI -9.74, -2.59.…”
Section: Discussioncontrasting
confidence: 50%
“…16 The Cochrane review 2017 also observed the duration of labour to be reduced by -10.64 minutes; 95% CI -20.15 to -1.12, in women using birth cushions for delivery compared to supine position. 21 The present study found a difference in favor of normal vaginal delivery and a decrease in the operative vaginal delivery in the kneeling position compared to the supine position; however, the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The review showed that using a flexible sacrum position can reduce the duration of the second stage of labor by 21.12. The reduction was contributed mainly by a large reduction in the three studies of the birthing ball, flexible sacrum and squatting positions reduce 25.9, 29.7 and 34.38 minutes respectively (22,27,28). The reduction in duration is in line with other review and meta-analysis conducted both in UK in different times (29,30), in contrast other meta-analysis done in Australia and UK, didn't show any reduction in duration of second stage (14,31).…”
Section: Discussionsupporting
confidence: 79%
“…All the included studies were conducted in health facilities. Among the 8 included studies, two studies compare squatting position Vs supine (21,22), two studies compare sitting position Vs supine, (23,24) one compare keeling Vs supine (25), two studies compare flexible sacral position Vs supine (26,27) and one study compare ambulation and birthing ball with supine position. Two studies allowed laboring women for free choice of birthing position (26,27).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Agregou-se na definição operacional a posição de cócoras, após sugestão de uma especialista, visto que essa é uma das posições assumidas pelas mulheres em processo de parto. (23,106,107)…”
Section: Auxílio E/ou Estímulo Para Mudanças De Posição Desejadas Durunclassified